Development and Validation of a Self-Neglect Scale Among Older People: The Study on Challenges for Neglect and Self-Neglect in Poland. (October 2021) - Zawisza, Katarzyna; Tobiasz-Adamczyk, Beata; Galas, Aleksander; Grodzicki, Tomasz
The study aimed to develop and validate a tool to recognize the presence and to evaluate the level of self-neglect in community-dwelling older people. The cross-sectional study included 2, 894 face-to-face interviews with randomly selected individuals from among the general population, social service users, and hospital patients. In addition, specially trained interviewers assessed the physical appearance and standards of living. Reliability, content, and construct validity were assessed. The Item Response Theory was used. The following scales were developed: the Self-Reported Self-Neglect Scale (SRSNS), the Objective Assessment of the Level of Self-Neglect–Physical Appearance (OALSN-PA) scale, concerning physical health risks based on the appearance of an individual, and the Objective Assessment of the Level of Self-Neglect–Standards of Living Arrangements (OALSN-SLA) scale, which assesses the physical and personal living conditions. The brevity of the scales makes them useful for the daily practice of health care and social care professionals.